1984
DOI: 10.1002/anie.198409731
|View full text |Cite
|
Sign up to set email alerts
|

Nonapentafulvalene by Oxidative Coupling of Cyclononatetraenide and Cyclopentadienide

Abstract: of the anion closely resembles that of [Moz05(o-benzened i~l a t e )~]~~~'~ and of [MoZO5(3,5-di-tert-1,2-benzenedioland possesses two cis-dioxomolybdenum(v1) centers bridged by one pz-oxido-and two pz-O-2-sulfidophenolate ligands. The last-mentioned bridges are asymmetr!c and involve Mo-0 distances of 2.117(2) and 2.482(2) A. The Mo atom has a very distorted octahedral environment of five 0 and one S donor atoms, with the largest and the smallest bond angles being 02Mo04'= 167.4(1)" and 03Mo04'= 67.q l ) O , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…[27] Because each of the rings contain 4n electrons the oxidative coupling approach to the parent, as demonstrated for the pentafulvalenes (Scheme 1), is applicable here. Escher and Neuenschwander showed that such coupling can be brought about, but use of five molar equivalents of sodium cyclopentadienide with one of 157 in the presence of 6.6 mol.…”
Section: Pentanonafulvalenesmentioning
confidence: 98%
See 2 more Smart Citations
“…[27] Because each of the rings contain 4n electrons the oxidative coupling approach to the parent, as demonstrated for the pentafulvalenes (Scheme 1), is applicable here. Escher and Neuenschwander showed that such coupling can be brought about, but use of five molar equivalents of sodium cyclopentadienide with one of 157 in the presence of 6.6 mol.…”
Section: Pentanonafulvalenesmentioning
confidence: 98%
“…equivalents of CuCl 2 in THF at -50°C results in the dihydro derivatives 165 and 14 (Scheme 36) with only traces of the [9.9] coupled molecule. [27,220] Scheme 36.…”
Section: Pentanonafulvalenesmentioning
confidence: 99%
See 1 more Smart Citation